Infiltração de diferentes substâncias ou agulhamento à seco em dor miofascial - uma revisão sistemática - Machado, Eduardo (2015)
The temporomandibular myofascial pain presents a major challenge in the diagnosis of temporomandibular disorders. Due to the characteristics of this condition, intramuscular injection procedures are often needed for adequate control of symptoms and treatment. Thus, the aim of this study was to evaluate the effectiveness of injection with different substances or dry needling in temporomandibular myofascial pain. The study design consisted of a systematic review of randomized clinical trials and research databases consulted were: Pubmed, EMBASE, CENTRAL/Cochrane, Lilacs, Scopus and Web of Science until October 2014. The selection of studies was carried out by two independent reviewers, who applied eligibility criteria to obtain the final sample of primary studies. After application of the inclusion criteria were selected fifteen studies. Due to the heterogeneity of the primary studies it was not possible to perform a meta-analysis. The narrative analysis of the results showed that most of the studies had methodological limitations and biases that have compromised the quality of its findings. Thus, there is a need of conducting further randomized clinical trials, with follow-up and larger samples, to evaluate the real effectiveness of the technique and evaluated substances.